Combined CO2 Capture and Hydrogenation to Methanol: Amine Immobilization Enables Easy Recycling of Active Elements. Issue 13 (4th April 2019) - Kar, Sayan; Goeppert, Alain; Prakash, G. K. Surya
Abstract: Amines were immobilized onto solid supports and employed for tandem CO2 capture and conversion to CH3 OH using homogeneous hydrogenation catalysts. The hydrogenation proceeded through the formation of formamide intermediates. After hydrogenation, the immobilized amines were easily filtered and collected to be reused. The catalyst and methanol were recovered from the filtrate. Covalently‐attached (to polymer support or silica) amine functionalities displayed the highest recycling potential with almost no leaching under the hydrogenation reaction conditions. Using polyethylenimine grafted onto a solid‐silica support, the catalyst and amine were successfully recycled, and CO2 (either pure or from the air) was efficiently captured and converted to CH3 OH over multiple cycles. Abstract : Amines hold their own : A recyclable system is reported for combined CO2 capture and its subsequent hydrogenation to methanol, based on amine immobilization onto solid supports. This new approach represents an alternative to the previously reported biphasic system and enables easy recycling of both the amine and catalyst components for a truly sustainable system.